Novel Influences of Sex and APOE Genotype on Spinal Plasticity and Recovery of Function after Spinal Cord Injury - Strattan, Lydia E. (eNeuro, 2021)
Spinal cord injuries can abolish both motor and sensory function throughout the body. Spontaneous recovery after injury is limited and can vary substantially between individuals. Despite an abundance of therapeutic approaches that have shown promise in preclinical models, there is currently a lack of effective treatment strategies that have been translated to restore function after spinal cord injury (SCI) in the human population. We hypothesized that sex and genetic background of injured individuals could impact how they respond to treatment strategies, presenting a barrier to translating therapies that are not tailored to the individual. One gene of particular interest is APOE, which has been extensively studied in the brain because of its allele-specific influences on synaptic plasticity, metabolism, inflammation, and neurodegeneration. Despite its prominence as a therapeutic target in brain injury and disease, little is known about how it influences neural plasticity and repair processes in the spinal cord. Using humanized mice, we examined how the ε3 and ε4 alleles of APOE influence the efficacy of therapeutic intermittent hypoxia (IH) in inducing spinally-mediated plasticity after cervical SCI (cSCI). IH is sufficient to enhance plasticity and restore motor function after experimental SCI in genetically similar rodent populations, but its effect in human subjects is more variable (Golder and Mitchell, 2005; Hayes et al., 2014). Our results demonstrate that both sex and APOE genotype determine the extent of respiratory motor plasticity that is elicited by IH, highlighting the importance of considering these clinically relevant variables when translating therapeutic approaches for the SCI community.